Almost Madam President: Why Hillary Clinton 'Won' in 2008 - Gutgold, Nichola D., (Lexington Books, 2009)
All around the world women are presidents and prime ministers, yet in America, we have yet to elect the first woman president. When Barack Obama accepted the nomination as the Democratic candidate for president in 2008, the media were quick to point out that Hillary Clinton lost. Yet Clinton won almost 18 million votes and was the first front- runner woman candidate. Almost Madam President: Why Hillary Clinton 'Won' in 2008 argues that Hillary Clinton gained more than she lost in her bid for the presidency. This book takes the reader on a rhetorical journey through Hillary Clinton's 2008 presidential campaign, focusing on Clinton's sophisticated 'You Tube' style announcement speech, the debates, and the many notable stump speeches and media events on the campaign trail. Along the way Gutgold examines the obstacles and opportunities of women as presidential candidates.